Carrier scattering mechanisms limiting mobility in hydrogen-doped indium oxide - Husein, Sebastian (2019)
Hydrogen-doped indium oxide (IO:H) has recently garnered attention as a high-performance transparent conducting oxide (TCO) and has been incorporated into a wide array of photovoltaic devices due to its high electron mobility (>100 cm2/V s) and transparency (>90% in the visible range). Here, we demonstrate IO:H thin-films deposited by sputtering with mobilities in the wide range of 10–100 cm2/V s and carrier densities of 4 × 1018 cm–3–4.5 × 1020 cm–3 with a large range of hydrogen incorporation. We use the temperature-dependent Hall mobility from 5 to 300 K to determine the limiting electron scattering mechanisms for each film and identify the temperature ranges over which these remain significant. We find that at high hydrogen concentrations, the grain size is reduced, causing the onset of grain boundary scattering. At lower hydrogen concentrations, a combination of ionized impurity and polar optical phonon scattering limits mobility. We find that the influence of ionized impurity scattering is reduced with the increasing hydrogen content, allowing a maximization of mobility >100 cm2/V s at moderate hydrogen incorporation amounts prior to the onset of grain boundary scattering. By investigating the parameter space of the hydrogen content, temperature, and grain size, we define the three distinct regions in which the grain boundary, ionized impurity, and polar optical phonon scattering operate in this high mobility TCO.